Imatinib mesylate in chronic myeloid leukemia: frontline treatment and long-term outcomes. Issue 3 (3rd March 2016) - Stagno, Fabio; Stella, Stefania; Spitaleri, Antonio; Pennisi, Maria Stella; Di Raimondo, Francesco; Vigneri, Paolo
SUMMARY: The tyrosine kinase inhibitor Imatinib Mesylate has dramatically improved the clinical outcome of chronic myeloid leukemia (CML) patients in the chronic phase of the disease, generating unprecedented rates of complete hematologic and cytogenetic responses and sustained reductions in BCR-ABL transcripts. Here, we present an overview on the efficacy and safety of Imatinib and describe the most important clinical studies employing this drug for the frontline treatment of chronic phase CML. We also discuss recent reports describing the long-term outcome of patients receiving Imatinib for their disease. The imminent availability of generic forms of Imatinib coupled with the approval of expensive second-generation tyrosine kinase inhibitors underlines an unmet need for early molecular parameters that may distinguish CML patients likely to benefit from the drug from those that should receive alternative forms of treatment.